Social and Emotional Learning and Academic Achievement in Portuguese Schools: A Bibliometric Study - Cristóvão, Ana M.; Candeias, Adelinda A.; Verdasca, José (Frontiers in Psychology, 2017)
Social and Emotional Learning (SEL) is an educational movement that is gaining ground throughout the world. We can define SEL as the capacity to recognize and manage emotions, solve problems effectively, and establish positive relationships with others. Research has demonstrated the significant role of SEL in promoting healthy student development and academic achievement. Extensive research confirms that SEL competencies: can be taught, that they promote positive development and reduce problem behaviors, and that they improve students’ academic achievement and citizenship. At the international level, several rigorous studies have identified programs and practices that promote SEL. In Portugal, however, no review has yet been published regarding the implementation of SEL programs. Such a study would elucidate the current panorama of SEL programs in Portugal. This study aims to identify research on SEL programs implemented in Portuguese schools and the relationship of those programs with academic achievement. To this end, we have consulted the following databases: Scientific Repository of Open Access of Portugal (RCAAP), Online Knowledge Library (b-on), and Web of Science (WoS). The criteria were: a) all time frames; b) publications in either Portuguese or English; c) programs that developed socio-emotional competencies in Portuguese schools; d) academic levels including elementary, middle, and high school and e) students of regular education. Few publications on SEL programs implemented in Portugal were found, although the recent decade has witnessed an upsurge of interest in the topic, principally that arising from academic research.